The Influence of Good Corporate Governance and Financial Performance on Firm Value - Saleh, Suji Abdullah; Maryanti, Lilis; Andhika Ligar Hardika (PT Larva Wijaya Penerbit, 2024)
Good Corporate Governance is a system that regulates the roles of the board of commissioners, the board of directors, shareholders, and other stakeholders. Every company is expected to implement Good Corporate Governance to support financial performance, which can also increase the company's value. However, some companies experienced performance issues and even losses, especially during the COVID-19 pandemic. In such a pandemic phenomenon, an alternative global financial system is needed, one of which is Islamic finance, which was also discussed during the global financial crisis of 2008-2009. This study aims to analyze the influence of good corporate governance, including variables such as the board of directors, institutional ownership, managerial ownership, audit committee, and audit quality, as well as financial performance measured by cash flow return on assets (CFROA) on firm value, and to compare the results between conventional and sharia banking. The type of this research is quantitative research with the research population being conventional and sharia banking listed on the Indonesia Stock Exchange for the period 2019 to 2023, with sampling using the purposive sampling technique. The data used are documentary data in the form of financial statements and annual reports. The analysis method used is multiple linear regression analysis, and hypothesis testing is conducted using the F statistical test (Simultaneously) and the t statistical test (partially) with the Eviews 12.